Tectonic reconstruction and sediment provenance of a far-travelled oceanic nappe, Helgeland Nappe Complex, west-central Norway - Kelsey L. McArthur; Carol D. Frost; Calvin G. Barnes; Tore Prestvik; Øystein Nordgulen (2016)
The Helgeland Nappe Complex (HNC), part of the Uppermost Allochthon of the north-central Norwegian Caledonides, originated near the Laurentian margin and was transferred to Baltica during the closure of Iapetus in Late Silurian–Early Devonian time. The islands of Rødøy, Bolvær and Leka, located in the Sauren–Torghatten (S–T) nappe of the HNC, are composed of ultramafic and mafic basement rocks unconformably overlain by metaconglomerates and fine-grained metasedimentary rocks. Geochemical and isotopic characteristics of the basement rocks are consistent with formation in a supra-subduction zone setting. Overlying metasedimentary rocks record an increasing proportion of continental detritus supplied to the basins through time. Precambrian cratonic source regions supplied cobbles and other detritus. This source area may have been located in modern SE Greenland/Labrador or in the Lower Nappe of the HNC. The second alternative best accounts for the short transport distances required by the coarse-grained conglomerates. The maximum age of deposition is constrained by the age of the youngest zircon grain dated at 471±8 Ma. Final sedimentation, nappe thrusting and nappe stacking occurred in rapid succession during c. 480–475 Ma.